2021
DOI: 10.1136/bmjopen-2020-046547
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of mental health in prisons through the COVID-19 pandemic

Abstract: ObjectiveTo examine the extent, nature and quality of literature on the impact of the COVID-19 pandemic on the mental health of imprisoned people and prison staff.DesignScoping review.Data sourcesPubMed, Embase, CINAHL, Global Health, Cochrane, PsycINFO, PsychExtra, Web of Science and Scopus were searched for any paper from 2019 onwards that focused on the mental health impact of COVID-19 on imprisoned people and prison staff. A grey literature search focused on international and government sources and profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 93 publications
3
75
0
1
Order By: Relevance
“…Based on our findings, increasing greening within and around prisons as well as improving the structure of windows are helpful. Besides, offering prisoners who are quarantined with better greenery views may help reduce mental illness and related consequences ( 8 ). On the other hand, though viewing nature was found beneficial, increasing the visibility of nature with extra greening may be costly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our findings, increasing greening within and around prisons as well as improving the structure of windows are helpful. Besides, offering prisoners who are quarantined with better greenery views may help reduce mental illness and related consequences ( 8 ). On the other hand, though viewing nature was found beneficial, increasing the visibility of nature with extra greening may be costly.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past year, prison visits and work were frequently suspended, making life in prison more restricted (7). Most prisoners stayed in small cells for more than 20 h a day (8). Infected prisoners were quarantined alone for dozens of days, which raised the concern of exacerbated mental health conditions, such as anger, depression, psychosis, self-harm, and suicide (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…National restrictions ( 3 ), in combination with pressure on national health services, resulted in changes in service provision and implementation, including changes in staff working patterns, physical distancing, telemedicine, admission and discharge procedures, and COVID-19 case detection and isolation ( 4 ). A scoping review of the literature examining the impact of COVID-19 in the prison population ( 5 ) suggested that imprisoned individuals were: (i) at a higher risk (compared to the normative population) of contracting COVID-19, related to living in confined spaces (overcrowded, poorly ventilated and often insanitary environments) and poorer physical heath; (ii) severely impacted by infection prevention and control measures which restricted access to each other and outside visitors, resulting in more isolation than normally experienced. The authors concluded that these conditions posed a huge challenge to the mental health of prisoners and staff working within prisons, and thus identified understanding the impact of COVID-19 and related restrictions as an urgent need ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Covid-19 pandemic has been called the worst public health crisis for a generation (Gatera & Pavarini, 2020;Heymann & Shindo, 2020;Lai et al, 2020), which has resulted in a number of measures including social distancing and lockdown measures within prison settings. The literature on Covid-19 in prison settings is emerging at the time of writing, with new studies published all the time, although these tend to be quite limited (Johnson et al, 2021). The majority of the emerging literature on Covid-19 in prison settings is health focused (Kakimoto et al, 2020;Okano & Blower, 2020;Vose et al, 2020) and often focused on different protocols and precautions that can, should and have been utilised to minimise the transmission of the virus in the prison setting (Burki, 2020;de Carvalho et al, 2020;Jones & Tulloch, 2020;Montoya-Barthelemy et al, 2020;Solis et al, 2020;Vose et al, 2020;Wang et al, 2020).…”
Section: Covid-19 In Prison Settingsmentioning
confidence: 99%